Effect Of Quality of Service on Loyalty Customers at PT. Pos (Persero) Lubuk Pakam Branch - Irfanni Hutasoit; Sari Wulandari (TALENTA Publisher, Universitas Sumatera Utara, 2022)
The purpose of this study was to determine whether there is an influence of service quality on customer loyalty at the Post Office (Persero) Lubuk Pakam Branch